2015
DOI: 10.1176/appi.ps.201400518
|View full text |Cite
|
Sign up to set email alerts
|

Two Birds, One Stone: Unintended Consequences and a Potential Solution for Problems With Recovery in Mental Health

Abstract: Recovery began as a social justice movement. In more recent years, professionals have joined the movement, unintentionally co-opting and mainstreaming the more radical goals of these earlier activist consumer movements. The goals of the patient-centered care movement in general medical care are similar to those of "professional recovery." If mental health professionals instead adopted the language and goals of patient-centered care as a first step toward joining the two movements, the recovery movement could r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(11 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…The activism associated with these claims asserts that mental health consumers/survivors have different and at times conflicting interests to those of professionals working within mainstream mental health services. Indeed, it has been suggested that the concept of recovery has been “stolen” by policy makers and mental health professionals, denying consumers opportunities for on-going activism or associated reform of the mental health system (Hunt and Resnick, 2015). Furthermore, it has been argued that the mainstreaming of recovery has “manufactured” a smoke screen that obscures the lack of substantive reform (Braslow, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The activism associated with these claims asserts that mental health consumers/survivors have different and at times conflicting interests to those of professionals working within mainstream mental health services. Indeed, it has been suggested that the concept of recovery has been “stolen” by policy makers and mental health professionals, denying consumers opportunities for on-going activism or associated reform of the mental health system (Hunt and Resnick, 2015). Furthermore, it has been argued that the mainstreaming of recovery has “manufactured” a smoke screen that obscures the lack of substantive reform (Braslow, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Patient involvement in mental health care is rooted in the widespread anti-psychiatry movement in the nineteen seventies (Hunt & Resnick, 2015;Oosterhuis & Gijswijt-Hofstra, 2008;Van Dijkum & Henkelman, 2010). The influence of this movement is still visible in patient organizations nowadays, especially in the plea for patient empowerment, recovery-oriented care, and the direct use of patient experience in mental health care.…”
Section: Patient Participation In (Dutch) Mental Health Carementioning
confidence: 99%
“…Patient involvement in mental health care is rooted in the widespread anti-psychiatry movement in the nineteen seventies (Hunt & Resnick, 2015;Oosterhuis & GijswijtHofstra, 2008;Van Dijkum & Henkelman, 2010). The influence of this movement is still visible in patient organizations nowadays, especially in the plea for patient empowerment, recovery-oriented care, and the direct use of patient experience in mental health care.…”
Section: Patient Participation In (Dutch) Mental Health Carementioning
confidence: 99%